A study on the recurrent laryngeal nerve injuries in thyroid surgeries at PESIMSR, Kuppam - Sonnepalli, Balaji; Francis, John M.; S., Shivananda (International Surgery Journal, 2019)
Background: Thyroid surgeries are routinely performed by general surgeons all over India. Although the incidence of recurrent laryngeal nerve (RLN) injury is uncommon, it still carries a significant impact on patient’s quality of life post operatively. Hence this study was done to identify and discuss incidence and various factors involved in RLN injury. Methods: This is a prospective observational study carried out at a rural health care setup at PES Institute of Medical Sciences and Research (PESIMSR), Kuppam. A total of 60 patients who qualified the inclusion and exclusion criteria were studied from December 2016 to June 2018. All the patient data including relevant history, clinical findings, intra operative findings and post-operative follow up were recorded and the results were tabulated. Institutional ethics committee clearance was obtained before the start of the study. Results: Out of 60 patients 51 were females and 9 were males. 30 patients had unilateral involvement and the other 30 patients had bilateral involvement of thyroid lobes on clinical and ultrasound examination. On fine needle aspiration cytology (FNAC), 57 were benign, 2 were malignant and 1 was Hashimoto’s thyroiditis. Surgeries were done according to standard protocol. Intra operatively RLN was identified in 56 patients. In 3 of them there was a structural anomaly. Postoperative hoarseness of voice was seen in 8 patients, however long term vocal cord palsy was seen in 3 patients. Conclusions: This study shows the importance of intra-operative nerve identification, incidence of RLN injury and role of postoperative rehabilitation.